Allogeneic stem cell transplantation for bone regeneration of a nonunion defect in a canine - Yaneselli K (Dove Medical Press, 2013)
Kevin Yaneselli,1 Andrea Filomeno,1 Gabriel Semiglia,1 Carolina Arce,1 Analía Rial,2 Natalia Muñoz,2 María Moreno,2 Kent Erickson,3 Jacqueline Maisonnave11Universidad de la República, Facultad de Veterinaria, Montevideo, Uruguay; 2Laboratory for Vaccine Research, Department of Biotechnology, Instituto de Higiene, Facultad de Medicina, Universidad de la República, Montevideo, Uruguay; 3University of California, Davis, CA, USAAbstract: Nonunion bone defects occur frequently with local pain, functional limitations, muscular atrophy, and fistulas due to osteomyelitis. The application of mesenchymal stem cells (MSCs) could improve regeneration of bone following bone defects. The objective of the present study was to evaluate the treatment of a nonunion defect due to chronic osteomyelitis in a greyhound female dog with allogeneic adipose tissue-derived mesenchymal stem cells (AT-MSCs). The implanted cells were adherent to plastic, were of fibroblast type, and expressed the canine stem cell markers CD90low, CD44high, and CD45-. Cell therapy consisted of five percutaneous weekly injections of 2 × 106 allogeneic AT-MSCs into the bone defect (total of 10 × 106 AT-MSCs). The patient was evaluated clinically and radiologically for up to 1 year. The results were clinical improvement, a light lameness score of 1 at week 16, return to use of its forearm, no pain, and increased muscular mass. No signs of osteomyelitis were observed radiologically and clinically there were no fistulas. There was no evidence of local or systemic adverse reactions caused by the aloimplants. The clinical relevance of the cell therapy contributing to repair of bone defects in small animals is a very promising future alternative. These results may have an important impact in new regenerative treatments for animal and human orthopedics.Keywords: allogeneic, AT-MSCs, treatment, nonunion, canine